The MoCA Memory Index Score: An Efficient Alternative to Paragraph Recall for the Detection Of Amnestic Mild Cognitive Impairment - Kaur, Antarpreet (Alzheimer Dis Assoc Disord, 2018)
OBJECTIVE: To compare ability of two measures of delayed memory (word list, story paragraph) to discriminate normal cognition from amnestic Mild Cognitive Impairment (aMCI). METHODS: Demographic, neuropsychological, and diagnostic data contributed by 34 Alzheimer’s Disease Centers (ADCs) to the National Alzheimer’s Coordinating Center (NACC) characterized 2,717 individuals with a diagnosis of either Normal Control (NC) (n=2,205) or aMCI (n=512). The Montreal Cognitive Assessment Memory Index Score (MoCA-MIS) assessed delayed word recall, and the Craft Story 21, delayed story recall. Logistic regression and receiver operator characteristic (ROC) curves controlling for age, sex and education assessed the ability of each test to differentiate NC and aMCI. RESULTS: The MoCA-MIS had significantly better sensitivity and specificity (area under the ROC curve 0.83 versus 0.80, p = 0.004). At sensitivity 80%, the specificity of the MoCA-MIS was 69.1%, compared to 62.8% for the Craft story. CONCLUSIONS: These data suggest that the MoCA-MIS, a recall score from items within the MoCA, is better at discriminating normal cognition from aMCI than the Craft Story. Word recall may be an efficient alternative to paragraph recall for diagnostic screening within clinical practice and research settings.